Revisiting the Impact of Divisional Affiliation on Secondary Market Ticket Prices in the National Football League - Yohan Lee; Moonsup Hyun; Stephen Shapiro; Alan Morse (Journal of Applied Sports Management, 2023)
With the emergence of demand-based ticket pricing, professional sport organizations and marketers will benefit from a thorough understanding of pricing in the demand-driven secondary market. Ticket pricing studies often take divisional affiliation as a control variable; little research has focused on and examined the importance of divisional affiliation for secondary market ticket prices. Different from work indicating consumers’ preference for divisional games, this study revealed that higher ticket prices (i.e., consumer demand) accompanied non-divisional games. Additionally, the number of years between the away team’s visit to the home team’s stadium and the away team’s current winning percentage each played a significant role (explained by roughly 49% of the variance) in higher ticket prices for non-divisional games in the National Football League.
Keywords: Secondary market ticket price; Dynamic pricing; Consumer demand; Divisional affiliation; National Football League